2003
DOI: 10.1002/jlcr.664
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of labelled 2‐methoxy‐3‐alkylpyrazines: synthesis and characterization of deuterated 2‐methoxy‐3‐isopropylyrazine and 2‐methoxy‐3‐isobutylpyrazine

Abstract: SummaryEfficient synthetic routes for a number of deuterated analogues of 2-methoxy-3-isopropylpyrazines and 2-methoxy-3-isobutylpyrazines have been developed involving the condensation of glyoxal with an a-amino acid amide followed by methylation with iodomethane. In this way [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(40 citation statements)
references
References 12 publications
5
35
0
Order By: Relevance
“…However, the products obtained showed different gas chromatographic (GC) properties compared with reference MPs 4a-c. This paper clarifies some of the previously published results and summarizes the chromatographic and spectroscopic characterization of compounds obtained by the method described by Gerritsma et al 16 and MPs, respectively their deuterated isotopologues.…”
Section: Introductionsupporting
confidence: 82%
See 4 more Smart Citations
“…However, the products obtained showed different gas chromatographic (GC) properties compared with reference MPs 4a-c. This paper clarifies some of the previously published results and summarizes the chromatographic and spectroscopic characterization of compounds obtained by the method described by Gerritsma et al 16 and MPs, respectively their deuterated isotopologues.…”
Section: Introductionsupporting
confidence: 82%
“…In our hands, the deuterated derivatives obtained after the approach of Gerritsma et al 16 ( Figure 1, route C) were not the designated MPs d 3 -4a-c, as they showed considerably higher retention indices after GC analysis, than those for the commercial non-deuterated MP reference substances. We obtained substances, which could later be assigned to the structures of d 3 -3a-c. Incorporation of deuterium into an organic molecule leads to a somewhat lowered retention index in gas liquid chromatography, despite its higher absolute molecular mass.…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations